Application of recombinant human basic fibroblast growth factor in repair of the aged dog bite wound. Issue 11 (November 2022) - Zhou, Chaoxi; Xia, Dong; Wang, Huiming; Jin, Hongju; Zhang, Wei; Ma, Jianhua; Wang, Qinglei; Zhao, Yongzhen
Abstract: Background: Dog bite wounds usually have severe local soft tissue damage and the wounds are likely to be contaminated by a large number of bacteria or even a series of rare pathogenic bacteria, leading to repeated infection and delayed wound healing. Recombinant human basic fibroblast growth factor (rh-bFGF) has excellent ability to promote wound repair and widely used in various complicated wounds. Objective: Observe the clinical efficacy of Recombinant human basic Fibroblast growth factor (rh-bFGF) applicated in the treatment of dog bite wounds. Methods: A total of 31 patients (16 adult and 15 aged) with rabies exposure grade Ⅲ dog bite wounds treated in the department of emergency surgery in our hospital from February 2020 to February 2022 were reviewed. Rh-bFGF was applied in the wounds after debridement and the patients were treated with preventive anti-inflammatory therapy. Observe the wound healing rules, infection rate, related complications and application time of antibiotics. Results: Eventually, all the wound were well healed and the healing time needed for most patients were about 2–3 weeks. The wound infection rate of aged patients was much higher, therefore application time of intravenous antibiotics injection in the aged patients was significantly higher than it in the adults (P < 0.05), but the difference of the time reach the intermittent wound dressing change was not statistically significant (P > 0.05). Conclusion: Rh-bFGF is safe and reliable for severe dog bite wounds in both the elderly and adults, it may help improve the early stage healing speed of aged patients, but the specific treatment needs to be individualized and accurate depends on different personal physique and wound conditions. Abstract : Rh-bFGF; Dog bite wound; Wound infection; Wound healing; Rabies exposure grade Ⅲ.